2020
DOI: 10.1093/database/baaa005
|View full text |Cite
|
Sign up to set email alerts
|

Predicted Drosophila Interactome Resource and web tool for functional interpretation of differentially expressed genes

Abstract: Drosophila melanogaster is a well-established model organism that is widely used in genetic studies. This species enjoys the availability of a wide range of research tools, well-annotated reference databases and highly similar gene circuitry to other insects. To facilitate molecular mechanism studies in Drosophila, we present the Predicted Drosophila Interactome Resource (PDIR), a database of high-quality predicted functional gene interactions. These interactions were inferred from evidence in 10 public databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…A high quality predicted interactome of D. melanogaster was downloaded from http://drosophila.biomedtzc.cn v2018_01 (last accessed 15 November 2021) [37]. Gene interaction networks were analyzed as undirected graphs with the igraph R package v1.2.5 [38].…”
Section: Gene Network Analysesmentioning
confidence: 99%
“…A high quality predicted interactome of D. melanogaster was downloaded from http://drosophila.biomedtzc.cn v2018_01 (last accessed 15 November 2021) [37]. Gene interaction networks were analyzed as undirected graphs with the igraph R package v1.2.5 [38].…”
Section: Gene Network Analysesmentioning
confidence: 99%
“…Several studies have been dedicated to understanding the interactome of this important species [13,188,198,307,[338][339][340][341][342][343][344][345][346][347][348][349][350][351][352][353][354][355]. The Drosophila Interactions Database (DroID) [355,356] and the Predicted Drosophila Interactome Resource (PDIR) are integrated database containing both experimental and predicted interactions [354].…”
Section: Insectsmentioning
confidence: 99%
“…Several studies have been dedicated to understanding the interactome of this important species [13,188,198,307,[338][339][340][341][342][343][344][345][346][347][348][349][350][351][352][353][354][355]. The Drosophila Interactions Database (DroID) [355,356] and the Predicted Drosophila Interactome Resource (PDIR) are integrated database containing both experimental and predicted interactions [354]. Interactome analyses have been applied to the disease vectors Glossina morsitans morsitans (tsetse flies) [290,291], Aedes aegypti [357][358][359] and Anopheles gambiae [13,188] (mosquitos), and the pests Acyrthosiphon pisum (aphid) and Tribolium castaneum (flour beetle) [13].…”
Section: Insectsmentioning
confidence: 99%
“…GO and KEGG analysis indicated that the four immune-related LncRNAs might be connected with several biological characteristics including acetylation, inflammatory response, protein binding, stimulatory C-type lectin receptor signaling pathway, cytoplasm, regulation of gene expression, epigenetics, mutagenesis site, isopeptide bond, cytosol, and erythrocyte differentiation through the DAVID web annotation tool ( Figures 5B,C ; Shao et al, 2018 ; Yuan et al, 2018 ). The analysis could help us to understand the potential molecular mechanisms of the four LncRNAs in the occurrence and development of HCC ( Ding et al, 2020 ).…”
Section: Gsea and Pca In The Whole Cohortmentioning
confidence: 99%